EFFICACY OF “QUYEN TY THANG” DECOCTION COMBINED WITH ELECTRO-ACUPUNCTURE AND KINESITHERAPY IN THE TREATMENT OF SIMPLE SCAPULOHUMERAL PERIARTHRITIS AT LANG GIANG MEDICAL CENTER (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic effects of the "Quyen Ty Thang" decoction combined with electroacupuncture and kinesiotherapy in the treatment of simple periarthritis of the shoulder.Subjects and Methods: The study included 60 patients with simple periarthritis of the shoulder treated as inpatients at the Department of Traditional Medicine and Rehabilitation, Lang Giang Medical Center, Bac Ninh, from February 2024 to November 2024. All patients were treated with electroacupuncture combined with kinesiotherapy, in which Group 1 consisted of 30 patients who used the "Quyen Ty Thang" decoction, and Group 2 consisted of 30 patients who did not.Results: In both groups, after 10 days of treatment, the range of motion (ROM) for shoulder abduction, internal rotation, and external rotation in the study group improved significantly compared to pre-treatment (p < 0.05). The ROM for shoulder abduction, internal rotation, and external rotation in the control group also improved significantly, with the improvement being statistically significant (p < 0.05). After treatment, the mean scores of the SPADI pain index, SPADI disability index, and total SPADI index in both groups showed significant improvement (p < 0.05). The rate of achieving "good" or better treatment results in Group 1 was 66.7%, which was significantly higher than the 30% observed in Group 2 (p < 0.05).Conclusion: The "Quyen Ty Thang" decoction combined with electroacupuncture and kinesiotherapy is effective in treating the simple form of periarthritis of the shoulder.
Keywords: Scapulohumeral periarthritis, Quyen Ty Thang decoction, electro-acupuncture, kinesitherapy.